A Psychophysical Approach to Discounting : Sex and Money. - Newquist, Matthew H. (My University, 2009)
Discounting has been defined as a decrease in the subjective value of an outcome as the delay to or uncertainty of receiving the outcome increases. Previous research on discounting indicates that when outcomes are delayed, money (a generalized conditioned reinforcer) retains its value longer than drugs and food which are consumable primary reinforcers. The present study extends previous research by using a psychophysical approach to examine how a primary reinforcer (sex) is discounted relative to a generalized conditioned reinforcer (money).
Color poster with text and graphs describing research conducted by Matthew H. Newquist, advised by Daniel P. Holt.
Keywords: Choice (Psychology); Delay of gratification; Motivation (Psychology); Sexual behavior--Psychological aspects; Money--Psychological aspects; Posters